KAMPUNG VERTIKAL DI MANGGARAI, JAKARTA SELATAN BERBASIS KONSEP ARSITEKTUR FLEKSIBEL (Vertical Kampung in Manggarai, South Jakarta Based on Flexible Architectural Concepts) - Yulianto P. Prihatmaji; Dini Agumsari (Unika Soegijapranata Semarang, 2016)
Population density is a phenomenon that occurs today in Jakarta. Visible from many slums located on marginal land. The problem of limited land in the settlement make residents should save space efficiently. In a case study of Kampung Manggarai South Jakarta, vertical housing planning based on flexible architectural concepts become solution to these problems. In addressing the problem of limited land, the theory by Carmona, et al in temporal dimension and Toekio in the concept of flexibility space, be a reference to solve the problems. Among them, continuity and stability on which the building must be sustainable and able adapt to their environment; expandability and implemented over time, that the building should be able to adapt to the needs of residents in a long time. Convertibility means buildings remain subject to change without massively overhauled. Versatility and time cycle and management which space activities are shown dynamically, as the user routine. Continuity and stability are applied to the orientation of the building mass, according to the site conditions through sustainable. A modular structure which allows the internal expansion and separation of space, adapting from concept expandability and implemented over time. Convertibility applied on the recommendation of the facade design, with non-permanent material. As well as the versatility and the time cycle and management embodied in the design of multi-functional furniture and dynamic space layout corresponding to routines occupants. Keywords: vertical housing, architectural flexibility, kampung culture Kepadatan penduduk merupakan fenomena yang terjadi saat ini di Kota Jakarta. Terlihat dari banyaknya permukiman kumuh yang berdiri di atas lahan marjinal. Permasalahan keterbatasan lahan pada permukiman membuat warga harus menghemat ruang secara efisien. Pada studi kasus di Manggarai Pasar, Jakarta Selatan perencanaan kampung vertikal dengan konsep arsitektur fleksibel dapat menjadi solusi permasalahan tersebut. Teori oleh Carmona, et al dalam temporal dimension dan Toekio dalam konsep fleksibilitas ruang menjadi acuan dalam mendesain. Diantaranya continuity and stability dimana bangunan harus dapat berkelanjutan dan mampu beradaptasi dengan lingkungannya; expandibility dan implemented over time yaitu bangunan harus dapat menyesuaikan kebutuhan penghuni dalam kurun waktu yang lama. Covertibility yaitu bangunan tetap dapat berubah tanpa harus dirombak secara besar-besaran. Serta Versatility dan time cycle and time management dimana aktivitas ruang diperlihatkan secara dinamis, sesuai rutinitas pengguna. Continuity and stability diterapkan pada orientasi massa bangunan, sesuai dengan kondisi site sehingga berkelanjutan. Struktur modular yang memungkinkan ekspansi internal dan pemisahan ruang, mengadaptasi dari konsep expandibility dan implemented over time. Convertibility terdapat pada rekomendasi desain fasad, dengan material non permanen. Serta versatility dan time cycle and management diwujudkan dalam desain furnitur multifungsi dan layout ruang yang terus berganti sesuai rutinitas penghuni. Kata Kunci: hunian vertikal, fleksibilitas arsitektur, budaya kampung